Employment Guaranteed? Social Protection during a Pandemic - Farzana Afridi; Kanika Mahajan; Nikita Sangwan (Institute of Labor Economics (IZA), 2021)
The Covid-19 pandemic has highlighted the potential of social protection programs in mitigating labor market shocks. We examine the role of one of the world's largest employment guarantee schemes, India's MG-NREGA, in cushioning job losses in one of the worst affected economies due to the pandemic. Our findings indicate that regions with greater historical state capacity to provide public workdays under the scheme generated relatively higher employment during the pandemic. Consequently, an increase in state capacity by one MG-NREGA workday per rural inhabitant in a district reduced job losses in rural areas in April-August 2020 by 7% overall and by 74% for rural women, over baseline employment rate. These cushioning effects strengthened as the mobility restrictions eased and were larger for women who were less mobile and less skilled. Our results suggest that employment guarantee programs can protect livelihoods, but for certain demographic groups relatively more than others depending on the nature and skill level of work offered.
Keywords: J68; H31; 330; employment; COVID-19; public employment guarantee; MG-NREGA; women